"A Song of Ice and Fire"—another verse from the world of ablation. (11th June 2019) - Saul, J. Philip; LaPage, Martin J.
Abstract: The debate between the use of radiofrequency (RF) or cryoenergy for ablation near the atrioventricular (AV) conducting system or small coronaries has been fueled by the relative efficacies and risks of the two technologies, particularly in smaller hearts. The manuscript by Schneider et al adds another chapter to that ongoing debate.